2009
DOI: 10.1186/1753-6561-3-s7-s91
|View full text |Cite
|
Sign up to set email alerts
|

A pathway analysis applied to Genetic Analysis Workshop 16 genome-wide rheumatoid arthritis data

Abstract: The identification of several hundred genomic regions affecting disease risk has proven the ability of genome-wide association studies have proven their ability to identify genetic contributors to disease. Currently, single-nucleotide polymorphism (SNP) association analysis is the most widely used method of genome-wide association data, but recent research shows that multi-marker tests of association may provide greater power, especially when more than one mutation is present within a gene and the mutations ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 17 publications
2
42
0
1
Order By: Relevance
“…Over the last few years pathway analysis has become an important tool in the analysis of GWAS and has successfully identified molecular pathways involved in human disease; for example, the identification of associations between immune-related pathways and Crohn's disease [28][29][30]36,37]. However, for other phenotypes, the results have been less reproducible.…”
Section: Future Science Groupmentioning
confidence: 99%
“…Over the last few years pathway analysis has become an important tool in the analysis of GWAS and has successfully identified molecular pathways involved in human disease; for example, the identification of associations between immune-related pathways and Crohn's disease [28][29][30]36,37]. However, for other phenotypes, the results have been less reproducible.…”
Section: Future Science Groupmentioning
confidence: 99%
“…RA affects approximately 1% of the adult population worldwide [2]. According to the National Institute of Arthritis and Musculoskeletal and Skin Diseases, about 1.3 million adults in the U.S. suffer from RA [3]. RA is a complex disease caused by a combination of genetic susceptibility and environmental factors [4].…”
Section: Introductionmentioning
confidence: 99%
“…We consider that the strong association between both diseases may be caused by shared genetic pathways. Fortunately, pathway-based method to study existing GWAS datasets has been applied into RA [3], [14], [15], [16], [17], [18], [19], [20]. However, no study reported the involvement of measles in RA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Ballard et al performed two pathway-based tests, a binomial test and a random set method to identify pathways associated with rheumatoid arthritis. 5 Wang et al utilized a modified gene set enrichment method for SNP data to identify pathways associated with Crohn's disease. 6 Both Wang et al and Dinu et al performed pathway-based analyses to study age-related macular degeneration.…”
Section: Introductionmentioning
confidence: 99%